THE IMPLICITY OF RELATIONSHIP BETWEEN TRANSPARENCY OF BANK LENDING TO THE REAL SECTOR AND ECONOMIC DEVELOPMENT: WORLD EXPERIENCE - Herasymenko, Alina (Socio-economic relations in the digital society, 2024)
The modern development of the global economy is associated with multiple transformational challenges that raise the issue of ensuring an appropriate level of mutual trust between banking and industrial businesses. This issue is especially relevant for Ukraine, which is facing a crucial task - the post-war reconstruction of the national economy on the basis of sustainability, integrity and environmental friendliness. The aim of the paper is to identify implicit links between the transparency of bank lending to the real sector and economic development over the past 15 years in twelve countries, including Ukraine. This study is based on the correlation and regression tools for analysing relationships. As a result, the article confirms the hypothesis of the existence of significant cause-and-effect relationships between improving banking transparency, reducing corruption, growing economic freedom, increasing lending to the real sector and ensuring economic growth for a number of countries, regardless of their level of economic development. It has been found that in countries with steadily high corruption and economic freedom perception indices, the significance of the correlation with the development of bank lending to the real sector is lost. The reasons for deviations from the natural dialectic of the studied relationships are revealed in the example of India and Turkey. The peculiarities of their formation, preconditions and prospects for strengthening in Ukraine are highlighted. The contribution of the National Bank of Ukraine to increasing the level of transparency of lending activities of second-tier banks is investigated.